2012
DOI: 10.1089/neu.2011.1890
|View full text |Cite
|
Sign up to set email alerts
|

The Utility of Near Infrared Spectroscopy in Detecting Intracranial Hemorrhage in Children

Abstract: A prospective case-control study was conducted in a tertiary care pediatric intensive care unit (PICU) to evaluate the use of near infrared spectroscopy (NIRS) for the detection of intracranial hemorrhage (ICH) in children. Subjects 0-14 years of age who had a computed tomography (CT) scan of the head performed as part of clinical care were eligible for enrollment. The children were stratified into two groups based on whether the CT was normal or abnormal. Children in the abnormal imaging cohort were further d… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

7
49
2

Year Published

2013
2013
2022
2022

Publication Types

Select...
4
3
1

Relationship

0
8

Authors

Journals

citations
Cited by 53 publications
(58 citation statements)
references
References 25 publications
7
49
2
Order By: Relevance
“…Fifty-nine patients in this cohort developed a secondary hematoma, with 93% (n = 55) of these cases identified by a positive DOD. Other similar investigations support these levels of sensitivity at * 90%, 30,31 with Salonia and coworkers 34 producing similarly sensitive and specific data in pediatric cases. NIRS, therefore, has exciting potential as a bedside screening tool for those individuals admitted after TBI to be observed for the development of secondary mass lesions, particularly if clinical examination is impractical because of sedation/general anesthesia, and if avoiding invasive intracranial monitoring is desired.…”
Section: Davies Et Alsupporting
confidence: 54%
See 2 more Smart Citations
“…Fifty-nine patients in this cohort developed a secondary hematoma, with 93% (n = 55) of these cases identified by a positive DOD. Other similar investigations support these levels of sensitivity at * 90%, 30,31 with Salonia and coworkers 34 producing similarly sensitive and specific data in pediatric cases. NIRS, therefore, has exciting potential as a bedside screening tool for those individuals admitted after TBI to be observed for the development of secondary mass lesions, particularly if clinical examination is impractical because of sedation/general anesthesia, and if avoiding invasive intracranial monitoring is desired.…”
Section: Davies Et Alsupporting
confidence: 54%
“…28 The profound effect that the presence of hematomas or intracranial mass lesions can have on the cerebral NIRS parameters yielded within the context of TBI has led to this modality being examined as a screening tool for the presence of these lesions since the early 1990s. [29][30][31][32][33][34] Primarily, these investigations examined the mean difference in optical density between each cerebral hemisphere (DOD) as a means of localizing pathology or predicting the presence of a localized hematoma or mass lesion. Within this area of study, work conducted by Robertson and coworkers 31 examined parameters retrieved from > 300 patients under observation after sustaining a TBI.…”
Section: Davies Et Almentioning
confidence: 99%
See 1 more Smart Citation
“…Therefore, a fast and portable device that could accurately detect the presence or absence of ICH, regardless of its ability to additionally provide detailed anatomical localization, would have clear clinical applications for (i) the identification and triage of ICH patients for hospital transport prioritization [14][15][16][17][18] and (ii) continuous monitoring of inpatients after ischemic stroke or neurosurgical procedures, to identify new onset or increased ICH in real time and expedite more detailed imaging and management. [19][20][21] Recent studies showed that near-infrared spectroscopy (NIRS) has potential as a portable diagnostic device to identify SDH and EDH rapidly because both occur superficial to the brain surface, [22][23][24] but NIRS cannot identify deep hemorrhages such as IPH and IVH. 25 A portable device that could identify both superficial and deep hemorrhages therefore represents an unmet need for ICH screening.…”
Section: Introductionmentioning
confidence: 99%
“…NIRS technology is also becoming smaller and more transportable for field use [34,35]. NIRS imaging has previously been developed for detecting intracranial hematomas based on the global optical density differences from a region on the head where there is a hematoma compared to a region where there is no hematoma [35][36][37][38][39][40][41]. One issue with this method is that in blunt trauma brain injury, when a patient is hit on one side of the head, a bruise or swelling appears on the side of the head that is hit and an intracranial hematoma may occur on the opposite side of the head, where the brain collides with the inside of the skull [42].…”
Section: Introductionmentioning
confidence: 99%